Establishing Incentive Structures and Planning Agencies That Support Market-Oriented Transformations - Isard, Peter (IMF Working Papers; Working Paper, 1991)
This note addresses various types of incentives that must be established before a market economy can function effectively. It also argues that the enormous challenge of restructuring large industrial enterprises or reabsorbing their workers, while appropriately based on market signals, cannot be accomplished by the market alone. Some type of planning will eventually be required. Ideally, such planning should receive high priority from the outset with clear recognition that durable macroeconomic stabilization will be very difficult to achieve in a democratic political system until the large state enterprises have been successfully transformed or their workers reabsorbed.